The left-side bias of face perception disappears in the perceptual matching task. - Xiong, Ruoling; Li, Shuzhen; Peng, Wenjie; Yuan, Jie (Visual Cognition, 2024)
Left-side bias is observed in explicit face processing. When viewing chimeric faces which consist of one side of a real face and its mirrored counterpart, individuals usually think the left chimeric face looks more like the real face. However, it remained unclear whether the left-side bias is present in implicit face processing. This study aimed to investigate it using a perceptual matching task and found that there was no evidence of a left-side bias in this task by two experiments. Then we further explored what the individual difference of this bias was related to and discovered that it was significantly related to one's own spatial bias in line bisection task. In conclusion, the left-side bias is present in explicit face processing, where it relies on external real face information. However, in implicit face processing, the left-side bias disappears and this bias is more closely linked to individual's own spatial bias.